Handbook of international business (John Wiley & Sons, 1982)
Assesses the factors driving international trade and competition, public policies affecting international markets, and other aspects of international business one needs to know to succeed in the increasingly competitive world market. Provides a broad perspective on international financial flows, balance of payments, and foreign exchange; and offers practical discussion of international codes of conduct and the roles of international economic institutions and foreign governments...